Analysis of Chlorophyll-a Distribution in Determining the Fishing District of (Euthynnus affinis) Using Satellite Images in North Sumatera Sea Flows - Arta, Fandi; Afriani, Afni; Karisma, Rizki (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2025)
The North Sumatra Sea waters are one of the potential areas for tuna (Euthynnus affinis) fisheries. However, fishermen's determination of fishing grounds still relies on traditional methods, such as observing seabirds and water color changes, which are often inaccurate. This study aims to determine chlorophyll-A distribution, the accuracy of tuna fishing areas, and the relationship between chlorophyll-A and catch using satellite imagery. This research is beneficial because it is helpful reference material for the fishing industry and the community regarding the relationship between chlorophyll-a and fishing grounds. This research was conducted from April 05 to April 29, 2024, using Aqua Modis satellite image data. The research method used was a survey method that was analyzed descriptively. The results obtained during the study showed that the highest chlorophyll-a concentration occurred in the period April 22 to April 29, 2024, with an average value of 8.71 mg/m3, and the lowest occurred in the period April 06 to April 13, 2024, with an average value of 4.83 mg/m3. Determination of the estimated fishing grounds for tuna (Euthynnus affinis) with overlay technique by shading the chlorophyll-a criteria area >0.1 mg/m3. The accuracy level of the estimation of tuna fishing grounds has an average accuracy of 52%. Chlorophyll-a and catches in North Sumatra Sea Waters have a very strong relationship with an R-value of 0.99